Restoring silvopastures with oak saplings: effects of mulch and diameter class on survival, growth, and annual leaf-nutrient patterns - Jiménez, M. N.; Pinto, J. R.; Ripoll, M. A.; Sanchez-Miranda, A.; Navarro, F. B. (Agroforestry Systems, 2014)
In Southwestern Spain, multifunctional silvopastoral systems consisting of pastureland and open oak woodlands are known as Dehesas. These, and other similar systems of the Mediterranean basin, are currently threatened by increasing intensive land use. As a consequence, oak regeneration is declining and is in need of adequate management and active restoration. Traditional restoration practices outplant one-year-old, nursery-produced oak seedlings grown in 250–350 cm3 containers, but establishment and growth results are typically poor. This work examines holm oak (Quercus ilex L. subsp. ballota (Desf.) Samp.) grown in a non-conventional container size (24 l) and age (6–7 years) with three mulch treatments (control, stone, and straw). In an open Dehesa of SE Spain, 106 oak saplings were planted in March 2010, and survival, diameter at breast height (DBH), and leaf-nutrient concentrations were analyzed. Forty months after planting, all treatments showed high survival (81 %) but only straw-mulched saplings differed significantly (94 %) from control (74 %). DBH increased over time but showed no significant differences among mulch treatments. Saplings with high initial DBH showed the greatest growth and change in DBH at the end of the study period. Leaf- nutrient concentrations changed significantly in the year following outplanting. Bi-monthly foliar nutrient concentration data show decreases in P, K, Zn, and B and sharp increases in Ca and Fe. In this work, we provide some evidence concerning the viability of non-conventional oak size for restoring, regenerating, or building up new agroforestry or silvopastoral systems. A combination of saplings with more than 10 mm of DBH and straw mulch is recommended.
Keywords: 10; 1007; ballota á saplings á; contains supple-; DBH; Dehesa; dehesa á mulch á; doi; electronic supplementary material the; Mulch; online version of; quercus ilex subsp; quercus ilex subsp. ballota; s10457-014-9737-y; Saplings; semi-arid; semi-arid á dbh á; Spain; this article

Post-fire salvage logging alters a key plant-animal interaction for forest regeneration - Castro, J.; Puerta-Pinero, C.; Leverkus, A. B.; Moreno-Rueda, G.; Sanchez-Miranda, A. (ECOSPHERE, 2012)
Post-fire salvage logging is widely implemented worldwide, but there is an increasing concern about its potential impact on the ecosystem. Moreover, there is scant information about the effect of salvage logging on ecosystem processes mediated by species interactions. We manipulated a burnt pine forest to experimentally analyze the effect of burnt-wood management on the colonization of Holm oak (Quercus ilex) mediated by acorn dispersal by Eurasian jays (Garrulus glandarius). Three replicates of three treatments were established in an 18-ha plot: salvage logging (SL), non-intervention (NI), and partial cut plus lopping (PCL; felling and lopping most of the trees but leaving all the biomass in situ). We hypothesized that different burnt-wood management could alter jays' landscape perception and thus the pattern of seed dispersal and seedling recruitment. We monitored jay abundance in each treatment for three winters and three breeding periods, and jay flights of potential acorn dispersal between nearby oak trees and the treatments. We also searched for oak seedlings recruited in the experimental plot for five years following the fire. Jays were recorded significantly more times (87%) in NI, and movements to this treatment during the acorn dispersal period were also more frequent (81% of the flights). Oak seedlings were also more abundant in NI (ca. 55%) than in SL or PCL (ca. 25% each), despite a strong effect of small remnants of live pines. The results show that the burnt forest, if unsalvaged, still provides a suitable habitat for jays, while salvage logging reduces the strength of this key plant-animal interaction for oak natural regeneration. Nonintervention policies after a forest fire therefore provide the opportunity for adaptive management that helps reduce restoration costs and increase the resilience of the system.
The following values have no corresponding Zotero field: pub-location: 1990 M STREET NW, STE 700, WASHINGTON, DC 20036 USA publisher: ECOLOGICAL SOC AMER
Keywords: Garrulus glandarius; jay-oak interaction; oak colonization; Quercus ilex; resilience; salvage harvesting; seed dispersal; Sierra Nevada National Park; succession